Pengaruh Implementasi Manajemen Berbasis Data Analitik Terhadap Pengambilan Keputusan Kepala Sekolah - Laila, Nur; Ramli, Akhmad; Bahrani, Bahrani (Universitas Pakuan, 2025)
THE EFFECT OF DATA-ANALYTIC-BASED MANAGEMENT IMPLEMENTATION ON SCHOOL PRINCIPALS’ DECISION-MAKING The development of information technology has brought significant changes to various aspects of life, including education. One positive impact of this technological advancement is the emergence of a data-analytic management approach that enables more accurate and efficient decision-making. This research employed a descriptive qualitative approach with a literature review as the primary data collection technique. This study was conducted by reviewing relevant scientific journals covering topics related to data management, principal leadership, and analytics-based decision-making. The researchers employed two theories: Simon's decision-making theory and Davis Olson's Management Information Systems theory. The results of this literature review indicate that the implementation of data-analytic management has a positive impact on principal decision-making. This approach enables principals to design more accurate, measurable, and evidence-based policies. Data literacy is a critical competency that supports the effectiveness of educational leadership. An integrated educational information system also strengthens the planning, implementation, and evaluation processes of school policies. Thus, data-analytic management serves as a strategic foundation for improving educational quality.